Effect of Levothyroxine on Blood Pressure in Patients With Subclinical Hypothyroidism: A Systematic Review and Meta-Analysis - He, Weiwei; Li, Sheli; Zhang, Jin-an; Zhang, Jing; Mu, Kaida; Li, Xin-ming (Frontiers in Endocrinology, 2018)
Background: Patients with subclinical hypothyroidism (SCH) have elevated blood pressure, but the effect of levothyroxine (LT4) therapy on blood pressure among those patients is still unclear. This study aimed to assess whether LT4 therapy could reduce blood pressure in SCH patients through a systematic review and meta-analysis. Methods: PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL) and Web of Science were searched. Randomized controlled trials (RCTs) assessing the effect of LT4 therapy on blood pressure or prospective follow-up studies comparing the blood pressure level before and after LT4 treatment were included, and the mean difference of systolic blood pressure (SBP) or diastolic blood pressure (DBP) was pooled using random-effect meta-analysis. Results: Twenty-nine studies including 10 RCTs and 19 prospective follow-up studies were eligible for the analysis. Meta-analysis of 10 RCTs suggested that LT4 therapy could significantly reduce SBP in SCH patients by 2.48 mmHg (95%CI -4.63 to -0.33, P = 0.024). No heterogeneity was observed among these 10 RCTs (I2 = 0%). Meta-analysis of the 19 prospective follow-up studies found that LT4 therapy significantly decreased SBP and DBP by 4.80 mmHg (95%CI -6.50 to -3.09, P < 0.001) and 2.74 mmHg (95%CI -4.06 to -1.43, P < 0.001), respectively. Conclusion: The findings suggest that LT4 replacement therapy can reduce blood pressure in SCH patients, which needs to be validated in more clinical trials with larger samples.